Monitoring the water quality of Belawan Sea for rearing asian seabass Lates calcarifer in a floating net cage system - Iman Sari Lubis, Vina; Nirmala, Kukuh; Supriyono, Eddy; Hastuti, Yuni Puji (Indonesian Society of Scientific Aquaculture (ISSA), 2024)
Belawan is a coastal area located in Medan Belawan District, North Sumatra Province. The aim of the research is to determine the feasibility status of the study location if it is developed as a location for floating net cages (KJA). The research was carried out in the sea waters of Belawan in August–September 2022. The research parameters observed during the research were hydrooceanographic data and water quality data including physical parameters, chemical parameters, biological parameters. Determination of water quality status using the STORET Index, CCME WQI Index and principal component analysis (PCA). Observation parameters during the research were clinical symptoms, histological observations and growth performance of Asian sea bass. The research results show that tides, COD and turbidity are parameters that do not comply with water quality standards. The types of phytoplankton consist of 15 species and 4 classes, namely Cyanophyceae, Chlorophyceae, Bacyllariophyceae and Dynophyceae. Observation total vibrio count (TVC) shows that in all water samples it is Log 105 CFU/mL and in snapper organs (gills, liver, kidneys) there are Log 104-105 CFU/g. The results of the research can be concluded that for each zone in Belawan waters there is no difference in the level of pollution between zones in terms of the STORET index (moderately polluted) and the CCME WQI index (marginal) with limiting factors namely COD and turbidity. Belawan waters are in less than suitable condition in August–September for snapper cultivation activities in floating net cages (KJA) characterized by low SR and ADG values. Keywords: Belawan Waters, CCME WQI index, STORET index, principal component analysis (PCA), water quality monitoring ABSTRAK Belawan termasuk kawasan pesisir yang terletak di Kecamatan Medan Belawan, Provinsi Sumatera Utara. Tujuan dari penelitian adalah untuk menentukan status kelayakan lokasi kajian jika dikembangkan sebagai lokasi keramba jaring apung (KJA). Penelitian dilaksanakan di perairan laut Belawan, Kota Medan yaitu pada bulan Agustus–September 2022. Metode pengambilan sampel dilakukan secara purposive sampling. Adapun parameter penelitian yang diamati selama penelitian yaitu data hidro oseanografi dan data kualitas air meliputi parameter fisika (konduktivitas, TDS, salinitas, suhu, kecerahan, kekeruhan), parameter kimia (DO, BOD, COD, amonia, pH), parameter biologi (plankton, TVC). Penilaian kualitas perairan menggunakan Indeks STORET, Indeks CCME WQI dan principal component analysis (PCA). Parameter pengamatan saat penelitian yaitu gejala klinis, pengamatan histologi dan kinerja pertumbuhan ikan kakap putih. Hasil penelitian menunjukkan bahwa pasang surut, COD dan kekeruhan merupakan parameter yang tidak sesuai dengan baku mutu kualitas air. Adapun jenis fitoplankton terdiri dari 15 spesies dan 4 kelas yaitu Cyanophyceae, Chlorophyceae, Bacyllariophyceae dan Dynophyceae. Pengamatan total vibrio count (TVC) menunjukkan bahwa pada seluruh sampel air yaitu Log 105 CFU/mL dan pada organ ikan kakap (insang, hati, ginjal) yaitu Log 104-105 CFU/g. Hasil penelitian dapat disimpulkan bahwa setiap zona dalam perairan Belawan tergolong tercemar sedang dan tidak terdapat perbedaan tingkat pencemaran ditinjau dari indeks STORET dan indeks CCME WQI dengan faktor pembatas yaitu COD dan kekeruhan. Berdasarkan hal tersebut, Perairan Belawan dalam kondisi kurang layak untuk kegiatan budidaya ikan kakap di keramba jaring apung (KJA) ditandai dengan nilai SR dan ADG yang rendah. Kata Kunci: indeks CCME WQI, indeks STORET, monitoring kualitas air, Perairan Belawan, principal component analysis (PCA)